Hubungan Supervisi Keperawatan dengan Kualitas Dokumentasi Asuhan Keperawatan di Ruang Rawat Inap Kemuning dan Dahlia Rsud Waled Kabupaten Cirebon - Ramli Effendi (Publikasi Indonesia, 2022)
Supervision is part of the direction of the management function so that all activities are carried out through information obtained by each staff. The implementation of supervision is carried out by supervisors to improve the quality of care by providing guidance, direction, teaching, motivating and improving nursing care in accordance with standard provisions. The purpose of this study aims to determine the relationship between nursing supervision and the quality of nursing documentation of inpatient wards. Kemuning and Dahlia Hospital Waled Cirebon Regency. The research method used was descriptive correlation with a cross sectional approach. The sample of this study was the executive nurse in the inpatient room Dahlia and Kemuning Waled Hospital Cirebon totaling 33 respondents using purposeful sampling technique. The tools used were questionnaires and observation tables, and the data were analyzed using the chi-square test. The results of the study showed that nursing supervision was good 57.6% and the quality of documentation was also good 60.6% after the statistical test resulted in a p value of 0.031 0.05 which showed a significant relationship between nursing supervision inpatient Kemuning and Dahlia Waled Hospital Cirebon district. Implementing and improving supervision activities can make nurses feel that someone is accompanying them, and this will also have a positive impact on the work of nurses on the quality of nursing care documentation.